Slow Clearance of Acylated, Hybrid Thrombolytic Enzymes - Robinson, Jeff H; Dodd, Ian; Esmail, Ashiq; Ferres, Harry; Nunn, Barbara (Thrombosis and Haemostasis, 1988)
Two hybrid plasminogen activators, plasmin A-chair/t-PA Bchain and plasmin A-chain/u-PA B-chain have been synthestzed and purified in sufficient yield to permit measurement of clearance in small laboratory animals. Each hybrid enzyme was reversibly acylated at the active centre to allow the pharmacokinetic profile to be followed using an activity-based method without interference from plasma inhibitors. The acylated plasmin/u-PA hybrid had a clearance half-life (t½) in guinea pigs of approximately 80 min, whereas acyl u-PA had a t½ of 3 min. The pharmacokinetic profile of the acylated plasmin/t-PA hybrid was measured in guinea pigs, rats and rabbits; the half-lives in all three species were 60–80 min compared to half-lives of acylated, native t-PA that were in the range 0.5–1.0 min. Thus, plasmin A-chaincontaining, acylated hybrid enzymes are cleared some 30- to 100-fold more slowly than the acylated parent activators.
Keywords: Fibrinolysis; Pharmacokinetics; Thrombolytic agents